Dynamisch Inter(- en Trans)disciplinair TaalOnderzoek. De nieuwe taalwetenschappen - Gontier, Nathalie (Academia Press, 2006)
Language research is currently in a state of flux. The phenomenon of language is not merely the topic of investigation in linguistics, it is examined by a multitude of scholars with different scientific backgrounds. In order to examine how these various disciplines approach language, a think-tank was founded in 2002, called DITO, Dynamisch Inter(-en trans)disciplinair onderzoek, or Dynamic Inter- (and trans)disciplinary Research. The think-tank is located at the Belgian Vrije Universiteit Brussel (Free University of Brussels). This book provides short introductory articles to the language research conducted by some of the think-tank's most important members, from within the point of view of the following 5 disciplines: philosophy of evolutionary biology, cognitive science, neuroscience, sign language research and artificial intelligence.